PENENTUAN KADAR VITAMIN C PADA MANGGA KWENI DENGAN MENGGUNAKAN METODE IODOMETRI - Uswatun Hasanah (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACT Vitamin C is one of the nutrients that role as antioxidant and effectively overcome the free radicals that can damage cells or tissue. Fruit is a good source of vitamin C, such as the mango kweni fruit. This study aimed to determine the levels of vitamin C in the mango kweni fruit using Iodimetry method. The results of the analysis of vitamin C in the mango kweni by using Iodimetry average was 3.48 g/100g.  Keywords: Vitamin C, Manggo kweni, Iodimetry.